The Comparison Of Students’ Academic Achievement Taught Using Jigsaw Versus Demonstration On Students’ Different Self-Confidence - Imam Azhar; Nafilatur Rohmah (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
The study investigated the effect of jigsaw cooperative learning method and students’ self-confidence on students’ academic achievement in fiqih in seventh grade of Junior Islamic High School. Three research questions and three hypothesis guided the study. The study used factorial design 2 x 3 which was a part of quasi experimental design. The subject research was 61 students that was devided into two groups by random assignment sampling. The instruments of study consisted questionaire and test. The questionaire was used to obtain the data of self-confidence, while test was used to gain the data of students’ academic achievement (outcomes). The questionaire contained 20 questions in accordance with compatibility and incompatibility of reaserch sample with the existing statement item while the test instrument contained 25 multiple choice questions. Both of instruments were pilot tested on the students to determine its usability as well as to gain its validity and realiability. The independent sample t-test was used to measure the mean scores of differences between achievement scores of experiment group and control group on pretest while the paired sample t-test was used to measure to measure the mean scores differences between achievement scores of experiment and control group on posttest. The two way analysis of varian (two-way anova) was used to measure the main effect (different teaching methods on students’ academic achievement) and interaction effect (different teaching methods and self-confidence on students’ academic achievement). The risults shew that jigsaw cooperative learning method helps students to obtain higher academic achievement than demontration teaching method. The risult was also revealed that the academic achievement of experiment group that at higer self-confidence gets higher score than another one. Lastly, there was not significant interaction effect between the two variables (teaching methods and self-confidence) on students’ academic achievement. Otherwise, it indicated that the two variables had a separate effect. This study recommanded that the next study should be done in accordance with these risults by adding or changing the independent variables